PERAN KBRI SEOUL DALAM PROMOSI BUDAYA DAN PARIWISATA INDONESIA DI KOREA SELATAN, 2015-2017 - Ni Luh Aulia Paquisa S (Jurusan Ilmu Hubungan Internasional, 2018)
This paper discusses the roles of the Indonesian Embassy in Seoul to promote Indonesian culture and tourism in South Korea on 2015-2017. Promoting Indonesian culture and tourism done by the Indonesian Embassy in Seoul are based on the 2nd Joint Commission Meeting held by Ministry of Foreign Affairs between the two countries in 2015. Through the meeting, both parties agreed to upgrade their bilateral cooperation in various fields including social-cultural field and tourism field. The role of the Indonesian Embassy in Seoul to promote Indonesian culture and tourism were done by doing several promotion events towards the particular sector. In cultural promotion, the Indonesian Embassy in Seoul used Indonesian arts as the means of the promotion. Meanwhile, in tourism promotion, Embassy of Indonesia in Seoul promote three particular sectors in tourism which are culinary tourism, sports tourism, and nature tourism as the means of promotion. The success done by the Indonesian Embassy are seen through the enthusiasm of the South Korean society in every cultural event held by the Indonesian Embassy, the increasing number of South Korean tourists, and the increasing frequency of flights between the two countries.